Utilization of Social Media for Digital Marketing Training as a Means of Increasing Knowledge of Wisatame Village Promotion - Nifa, Kholishotun; Sunardi, Sunardi; Setiawan, Abdul Haris (Universitas Sebelas Maret, 2023)
After the COVID-19 pandemic, education and training in Indonesia is conducted online. To ensure that the learning experience remains meaningful, various learning media must be used properly. Therefore, the use of social media among the community has increased rap-idly, which allows them to use it as a learning medium. There are three tourism village man-agers involved in this study, namely the chairperson, secretary and treasurer. The purpose of this study was to find out the participants about the utilization of social media before and after using it as a learning or digital marketing training to increase their knowledge about tourism village promotion. This study used a qualitative approach, data were collected through interviews, observations, and literature studies. The results showed that social media is very effective as a source of digital mark eting learning to increase promotional knowledge and this training can equip participants in promoting existing tourist villages.